(untitled) (Research, Society and Development, 2022)
Urbanization represents a threat to biodiversity, as built-up areas differ significantly from the natural environment. Therefore, it is necessary to produce ecological data for more conservationist urban management, i.e., promoting and maintaining biodiversity. In this sense, we carry out a tree documentation in 10 urban forest areas, i.e., reforestation, regenerated forests, and remnants of Seasonal Semideciduous Atlantic Forest, from Presidente Prudente, west of the state of São Paulo, southeast of Brazil. Using the quadrant method and different diversity indices, we found a considerable richness and diversity of native tree species in reforestation, especially in remnants. In one of these remnants, there is even an endangered tree species. However, there are regenerated forests whose trees are of a single exotic species with invasive traits. The phytosanitary status of many of these trees suggests a prominent potential for spreading. The remnant urban forests are priority references for conservation actions to promote and maintain biodiversity in the city.